New supplements for the formate mutant of Neurospora. A possible role for ascorbic acid? - D. Newmeyer; V. C. Pollard; David D. Perkins (Fungal Genetics Reports, 1988)
Recently we found what appeared to be a new auxotroph in one of our stocks. It was eventually traced to the formate (for) locus.